Internal and Cross-Border Conflict of Laws Regulation in the United States of America - CHUMACHENKO, Ivan (Journal of Advanced Research in Law and Economics, 2020)
The relevance of the research is due to the development of cross-border economy relations with involvement of the United States residents and the residents of other countries. Such an interest considers the questions about the correct choice of the applicable law in the framework of legal relations with the participation of U.S. residents carried out in the territory or residents of the different countries covered by the jurisdiction of the United States. The authors objectives under this article is to consider the basic concepts, as well as some features of resolving conflicts arising between the provisions of the U.S. Federal law, the laws of certain U.S. states with the laws of other countries, as well as, in some cases, with international law. In the framework of the study, the author used various methods, in particular, the dialectical method, methods of analysis, synthesis, the formal legal method, the comparative legal method, as well as the method of analyses of legal acts and judicial precedents. The basic method used in the paper is a comparative method. By applying of this method, the author tries to show the differences between US legislation (as the common law system country) and continental (civil) law countries in relation to the resolving of the conflicts of law. By using of the comparative method, the author also tried to show the differences between the English and the U.S. law. The comparative method also compared with the method of analyses by using of this method the author examined the features of conflict resolution in accordance with statutory legislation, judicial precedents, as well as U.S. doctrine sources. The author provides the basic concepts regarding to the law on conflicts, which contain the main approaches to resolving the conflict of various jurisdictions in the United States. As the results of the research, the author concludes that even if there are separate (special) legal acts, judicial cases, as well as doctrine sources that, it would seem, should help overcome conflicts between different legal systems, given the diversity of legal relations, such collisions will arise in the future, which will push lawmakers to further develop issues of U.S. ‘law on conflicts’ or ‘conflict of laws’.